2018
DOI: 10.7554/elife.38801
|View full text |Cite
|
Sign up to set email alerts
|

Rap2 and TNIK control Plexin-dependent tiled synaptic innervation in C. elegans

Abstract: During development, neurons form synapses with their fate-determined targets. While we begin to elucidate the mechanisms by which extracellular ligand-receptor interactions enhance synapse specificity by inhibiting synaptogenesis, our knowledge about their intracellular mechanisms remains limited. Here we show that Rap2 GTPase (rap-2) and its effector, TNIK (mig-15), act genetically downstream of Plexin (plx-1) to restrict presynaptic assembly and to form tiled synaptic innervation in C. elegans. Both constitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 92 publications
1
23
0
Order By: Relevance
“…In CNS synapses Tnik is concentrated in the postsynaptic density [81]. However, decreases in the frequency of miniature excitatory postsynaptic currents in Tnik -/mice and Tnik's ability to regulate the number of synapses in Caenorhabditis elegans suggest a role of Tnik in presynaptic processes [81,94]. Therefore, a possible functional link between TNIK and presynaptic calcium channels commonly regulating neurotransmitter release may exist.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…In CNS synapses Tnik is concentrated in the postsynaptic density [81]. However, decreases in the frequency of miniature excitatory postsynaptic currents in Tnik -/mice and Tnik's ability to regulate the number of synapses in Caenorhabditis elegans suggest a role of Tnik in presynaptic processes [81,94]. Therefore, a possible functional link between TNIK and presynaptic calcium channels commonly regulating neurotransmitter release may exist.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…The DA neurons extend axons within the dorsal nerve cord, where they form en passant synapses at specific subaxonal regions onto the dorsal body wall muscles ( White et al, 1976 ). Previous electron microscopy reconstruction and fluorescent microscopy has revealed the tiled synaptic innervation pattern between neighboring DA neurons: the axonal region with synapses (synaptic domain) of a DA neuron does not overlap with those of its neighboring DA neurons ( Chen et al, 2018 ; Mizumoto and Shen, 2013a ; White et al, 1976 ). In this study we generated a new transgene ( mizIs3 ) with improved color contrast between the two most posterior DA neurons, DA8 and DA9, under the fluorescent microscope.…”
Section: Resultsmentioning
confidence: 99%
“…DA neurons exhibit a unique ‘tiled’ synaptic innervation pattern, in which the synaptic domain of a DA neuron does not overlap with those from the neighboring DA neurons ( White et al, 1976 ; Figure 1A ). Previously, we have shown that the interaxonal interaction between two DA neurons (DA8 and DA9) mediated by Semaphorin–Plexin signaling establishes the synaptic tiling of DA8 and DA9 ( Chen et al, 2018 ; Mizumoto and Shen, 2013a ). In the loss of function mutants of unc-4 and unc-37, we show that the tiled synaptic innervation between DA8 and DA9 is severely disrupted, similar to the mutants of Semaphorin-Plexin signaling components.…”
Section: Introductionmentioning
confidence: 99%
“…The C. elegans cholinergic motor neuron DA9 resides in the preanal ganglion, from where it extends a dendrite in the ventral cord and an axon that traverses across to the dorsal cord and grows anteriorly, establishing ∼25 en passant presynaptic sites onto dorsal muscles at stereotypic positions (Figure 1A) (White et al, 1986). Expression of the active zone protein Clarinet-1 (CLA-1), homolog of mammalian Piccolo and Bassoon, and the SVP marker RAB-3 allow to visualize DA9 synapses at a single-cell resolution (Chen et al, 2018; Kurshan et al, 2018; Xuan et al, 2017) (Figure 1B). In DA9, the sole C. elegans Neurexin, nrx-1 , is required presynaptically for at least two known functions: clustering of RAB-3 vesicles and preventing loss of proximal synaptic boutons (Kurshan et al, 2018) (Figure 1E).…”
Section: Resultsmentioning
confidence: 99%